(untitled) (Journal of the College of Basic Education, 2022)
The research consists of four chapters with a list of sources. The first chapter deals with the methodological framework, which deals with the research problem that revolves around how the aesthetics of music overlap with the aesthetics of the actor’s vocal and kinetic performance when he expresses a specific dramatic situation. The researcher noticed that there are a number of novice actors who do not have enough ability to create This compatibility is due to the lack of aesthetic taste experience of the actor, on the one hand, and lack of knowledge of the musical currents, their overlap and their chronological development, on the one hand, their historical heritage, and the characteristics of people’s melodies, on the other hand.